Self-set salaries and creativity - Christian Brück; Thorsten Knauer; Harald Meier; Anja Schwering (Journal of Business Economics, 2020)
Organizations frequently try to incentivize employees to develop highly creative solutions. In this study, we examine self-set salaries as a specific type of incentive design. We investigate whether self-set salaries affect employees' motivation and overall (creative) performance. Moreover, because self-set salaries potentially risk opportunistic employee behavior, we consider the effect of the observability of peer performance on employees' level of self-set salaries. Using a laboratory experiment, we hold the average employee compensation constant and demonstrate that, in comparison with fixed-pay contracts, self-set salaries increase the quantitative performance in creative tasks without affecting the average creativity. However, we do not find significant differences between the amount of individuals' self-set salaries with observability of peer performance and the amount for individuals without the chance to observe peer performance. Our findings are important for firms that rely on the development of creative ideas but are unsure about the effects of the introduction of self-set salaries.
Keywords: C91; M40; M41; 650; Creativity; Incentives; Self-set salaries; Employee participation; Autonomy